Transparent Flexible Graphene Triboelectric Nanogenerators. (28th March 2014) - Kim, Seongsu; Gupta, Manoj Kumar; Lee, Keun Young; Sohn, Ahrum; Kim, Tae Yun; Shin, Kyung‐Sik; Kim, Dohwan; Kim, Sung Kyun; Lee, Kang Hyuck; Shin, Hyeon‐Jin; Kim, Dong‐Wook; Kim, Sang‐Woo
<x xml:space="preserve">Abstract</x> Transparent flexible graphene triboelectric nanogenerators as new promising applications of chemical vapor deposition‐grown graphene are successfully demonstrated. The work function and friction are decisive factors to understand the difference in output performance depending on the number of layers of graphene. In this work, we were able to power an LCD, LEDs, and an EL display using the electrical power output of the graphene triboelectric nanogenerator without any external energy source. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>